Compelling Evidence Linking CD40 Gene With Graves’ Disease in the Chinese Han Population - Jiang, He; Yuan, Fei-Fei; Wang, Hai-Ning; Liu, Wei; Ye, Xiao-Ping; Yang, Shao-Ying; Xie, Hui-Jun; Yu, Sha-Sha; Ma, Yu-Ru; Zhang, Le-Le; Zhao, Shuang-Xia; Song, Huai-Dong; et al. (Frontiers in Endocrinology, 2021)
Mutations in CD40 have been widely reported to be risk factors for Graves’ disease (GD). The gene, along with its cognate ligand CD40L, may regulate pro-inflammatory and immune responses. Rs1883832, located at the -1 position of the Kozak sequence, is the most well-studied single nucleotide polymorphism (SNP) of CD40, and has been confirmed to predispose those with the alteration to GD, regardless of ethnicity. Our genome-wide association study (GWAS) indicated that several SNPs, including rs1883832 located within the vicinity of CD40 were associated with GD in the Han Chinese population. Aiming at identifying the most consequential SNP and its underlying pathogenic mechanism, we performed a two-stage refined study on 8,171 patients with GD and 7,906 controls, and found rs1883832 was the most significantly GD-associated SNP in the CD40 gene region (PCombined = 9.17×10-11, OR = 1.18). Through searching the cis-expression quantitative trait locus database and using quantitative RT-PCR, we further discovered that the rs1883832 genotype can influence CD40 gene transcription. Furthermore, we demonstrated that rs1883832 is a susceptibility locus for pTRAb+ GD patients. In conclusion, the current study provides robust evidence that rs1883832 can regulate CD40 gene expression and affect serum TRAb levels, which ultimately contributes to the development of GD.